Preparation and evaluation of clean briquettes from disposed wood wastes. Issue 20 (18th October 2017) - Shiferaw, Yoseph; Tedla, Abebe; Melese, Chala; Mengistu, Atakilt; Debay, Beletie; Selamawi, Ybiralm; Merene, Efoyta; Awoi, Nejat
ABSTRACT: This study reports charcoal briquettes preparation from wood wastes and the evaluation of their quality to be used as clean energy source, as well as the availability of raw biomass materials. The accessibility of raw materials (biomass) was assessed through survey and interview. The collected materials were carbonized and then powdered using an electric milling machine and mixed with various binders in different proportions. The proximate analyses of the resulting briquettes were determined in accordance with ASTM analytical methods. Volatile matter (11.30–26.00%), ash content (4.67–26.67%), moisture content (2.67–7.67%), and fixed carbon (44.27–72.00%) of the charcoal briquettes were obtained. Gross heat (calorific value) was also measured using a Parr Isoperibol Bomb Calorimeter and found to be in the range 6940.77–8930.55 cal/g. Compared with traditional wood charcoal, all the briquettes prepared in this study were efficient with long burning time, having no smoke, spark, and odor. The results indicate the availability of raw materials, and that the quality parameters of the prepared briquettes were within the internationally recommended limits, suggesting the possibility of producing high-quality charcoal briquette as an alternative energy source and a way for waste management.